Revitalization Of Local Wisdom (Lubuk Prohibition) In Maqashid Al-Sharia'ah Review Of The Welfare Of The Muslim Community - Nawir Yuslem; Nurhayati Nurhayati; Elwardi Hasibuan (Eduvest - Journal of Universal Studies, 2022)
Lubuk prohibits one of the local wisdoms of the people of Mandailing Natal Regency in environmental utilization. So far, the pits of prohibition have been managed naturally and traditionally, considering the large amount of damage caused by illegal miners. To anticipate more fatal damage, institutional revitalization is needed. The purpose of this study is to analyze the management of lubuk prohibition in realizing maqashid sharia and its role in improving the welfare of society. This research is a qualitative research with an ethnographic approach and uses a case study method. Sources of research data were obtained through in-depth interviews with key informants, namely Government Officials, Customary Leaders, Lubuk Ban Managers, Community Leaders and Naposo Nauli Bulung and other informants who understand and are related to this research. Another method used to support the results of interviews in informal FGD forums is field observation and documentation. The results showed that the management practice of Lubuk Ban in Mandailing Natal Regency has changed into a new, more rational format with management based on religious beliefs (Religious/Islamic).